Characterization of a thermostable uricase derived from Thermoactinospora rubra YIM 77501T and its heat-resistant mechanism - Yan, Xin; Tang, Lan-Xin; Ortúzar, Maite; Yang, Li-Quan; Sang, Peng; Jin, Na-Ying; Li, Lin-Hua; Yang, Zheng-Feng; Wang, Yan-Wen; Li, Wen-Jun; Hu, Wei; Yin, Yi-Rui (Frontiers in Microbiology, 2025)
IntroductionUricases are oxidative enzymes that catalyze the conversion of uric acid to allantoin and hydrogen peroxide, widely utilized in uric acid testing and the treatment of gout, hyperuricemia, and Tumor Lysis Syndrome (TLS). The search for uricases with long-term thermostability has become a significant area of research.MethodsIn this study, a uricase gene (truox) was obtained from the genome of Thermoactinospora rubra YIM 77501T, which was subsequently cloned and heterologously expressed. The resulting enzyme, TrUox, was comprehensively characterized for its biochemical properties and analyzed through molecular dynamics (MD) simulations.ResultsTrUox exhibits maximal catalytic activity at 35°C and pH 7.6 (mesophilic range). Notably, its thermostability is exceptional: the enzyme retains over 90% residual activity after 4 days of incubation at 50°C (with activity measured post-thermal treatment at 35°C) and maintains >90% activity for 10 days at physiological temperature (37°C). In vitro, 1.14 μg/mL TrUox effectively lowered serum uric acid (UA) from >700 to < 420 μM within 2 h in hyperuricemic models. MD simulations comparing TrUox with Rasburicase indicate it's more rigid/stable globally, less flexible, has fewer sub-states, and is more stable in FEL.DiscussionThese results demonstrate TrUox as a robust uricase exhibiting dual advantages of catalytic efficiency and enhanced thermostability, positioning it as a promising biocatalyst for industrial-scale production and therapeutic development. Our preliminary study into its thermostable mechanism provides a theoretical foundation for future production and research.